2005
DOI: 10.1128/mcb.25.9.3431-3442.2005
|View full text |Cite
|
Sign up to set email alerts
|

Recql5 and Blm RecQ DNA Helicases Have Nonredundant Roles in Suppressing Crossovers

Abstract: In eukaryotes, crossovers in mitotic cells can have deleterious consequences and therefore must be suppressed. Mutations in BLM give rise to Bloom syndrome, a disease that is characterized by an elevated rate of crossovers and increased cancer susceptibility. However, simple eukaryotes such as Saccharomyces cerevisiae have multiple pathways for suppressing crossovers, suggesting that mammals also have multiple pathways for controlling crossovers in their mitotic cells. We show here that in mouse embryonic stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
133
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 61 publications
8
133
2
Order By: Relevance
“…It also suggests that the main function of Recql5 with respect to suppressing SCEs does not lie at the dissolution of DHJ, a deduction that is consistent with our previous finding that Blm and Recql5 have nonredundant roles in suppressing SCEs in mitotic cells (Hu et al 2005). …”
Section: Recql5 Deficiency Is Not Associated With An Elevated Frequensupporting
confidence: 78%
See 2 more Smart Citations
“…It also suggests that the main function of Recql5 with respect to suppressing SCEs does not lie at the dissolution of DHJ, a deduction that is consistent with our previous finding that Blm and Recql5 have nonredundant roles in suppressing SCEs in mitotic cells (Hu et al 2005). …”
Section: Recql5 Deficiency Is Not Associated With An Elevated Frequensupporting
confidence: 78%
“…Therefore, while BLM likely represents the Sgs1 ortholog, the other RECQ-like helicases represent potential candidates as the functional equivalent of Srs2 in humans. We recently reported that mouse cells deficient in the RECQL5 homolog Recql5 exhibit an elevated level of SCEs, thus implicating this helicase in the regulation of HR (Hu et al 2005). Importantly, deletion of both Recql5 and Blm further increases the SCE frequency, consistent with Recql5 acting to regulate SCEs in mitotic cells via a mechanism that is distinct from Blm, perhaps by functioning similarly to Srs2 to suppress the channeling of DNA lesions into HR.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…RECQ5 is important for preventing both transcription-associated DSBs and DSBs induced by TOP1 poisons, such as camptothecin (CPT) [15][16][17] . The increased DSB formation observed in Recq5-deficient cells may contribute to elevated frequencies of homologous recombination and genome rearrangements 12,16 .…”
mentioning
confidence: 99%
“…RECQ5 is important for preventing both transcription-associated DSBs and DSBs induced by TOP1 poisons, such as camptothecin (CPT) [15][16][17] . The increased DSB formation observed in Recq5-deficient cells may contribute to elevated frequencies of homologous recombination and genome rearrangements 12,16 . RECQ5 prevents transcription-associated DSBs by suppressing RNAPII-dependent transcription initiation 18 , and this may be achieved by the interaction between RNAPII and the RECQ5 KIX domain, which blocks the binding of transcription elongation factor TFIIS to RNAPII 19 .…”
mentioning
confidence: 99%